Imputação de danos na omissão estatal - Bedone, Igor Volpato (2013)
This essay focuses on the attribution of liability to the State for its omissive conduct. The main objective is to discuss whether State omission gives rise to strict liability or fault liability, a question that is the subject of a well-known controversy in legal doctrine, echoed by jurisprudence. The methodology employed is essentially dogmatic, and I have chosen to build this essay on Civil Law concepts such as conduct, causation and liability. The underlying purpose is to compare such concepts with those of Administrative Law, the branch of law which establishes the general boundaries of civil liability of the State. If some writers argue that omission is characterized by a duty to act which, if breached, imposes fault liability, one must study what is fault and when an omissive conduct becomes relevant from a Civil Law perspective. In the end, it will be shown that the debate is wrongly centered on the subjective element of fault, when it should focus on causation, or rather on attribution of liability. The importance of the causes for not imposing liability as part of the process of assessing the State s liability for omission is also discussed